(untitled) (Bangladesh Journal of Medical Science, 2025)
INTRODUCTION Periodontitis is an inflammatory disease caused by specific bacteria that leads to the progressive destruction of toothsupporting tissue. Treatment often includes non-surgical therapy, but antimicrobials may be needed to target bacteria. However, antimicrobial resistance can occur. Statins, particularly lovastatin, have shown promise in reducing inflammation and promoting bone formation in periodontitis treatment. Methods This study included 62 patients (12 males, 50 females) with chronic localized periodontitis aged 29-41. Patients were randomly divided into two groups: one treated with lovastatin gel (experiment group) and the other with a placebo (control group). After baseline measurements, subgingival scaling and gel application were performed. Data was analyzed using SPSS software (IBM SPSS Statistics for Windows, Version 22.0.Armonk, NY: IBM Corp.). Results This longitudinal study evaluated the efficacy of subgingival lovastatin in treating chronic localized moderate periodontitis. The study included 62 patients with no significant baseline differences. Significant improvements were observed in the lovastatin-treated experimental group for sulcus bleeding, pocket probing depth, clinical attachment, and bone fill (93.5% vs. 29% in the control group) Conclusion The study concludes that lovastatin’s local delivery adjunct to scaling and root planning reduces bleeding pocket depth and enhances clinical attachment and bone growth. Long-term, more extensive studies are needed to assess its full benefits. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 413-422